Policy national solid waste as tool for regional sustainable development - Dandaro, Fernando (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The National Solid Waste Policy, established in August 2010, aims to standardize, give guidelines, goals and actions for the integrated management and solid waste management. Its applicability becomes of great viability within a context of capital accumulation and excess consumption, withthe purpose of protecting the environment in a sustainable way, contributing to the economic, social and environmental development. The objective of this study is to perform a study on the intentions of PNRS (National Solid Waste Policy) as a tool for Sustainable Regional Development guided the reverse logistics process. Therefore, the methodological procedures used are: bibliographicaland documentary research with qualitative approach and content analysis. This approach is justified by the subject of visibility today, as well as the need for a systemic view of the law given its complexity and requirement to emulate sustainable development through reverse logistics and actionsof the various agents forward the proposals of the National Policy Solid Waste to turn waste into economically aggregate assets of social value.